The Asteraceae family in the Flora of the Bajio and adjacent regions - Villaseñor, José Luis; Ortiz, Enrique (Instituto de Ecología, A.C., 2012)
Based on herbarium specimens identified and georeferenced, collected in the territory considered for the Flora of the Bajío and adjacent regions project, the family Asteraceae richness known for the region is analyzed. The area was divided in grid squares of 0.5° x 0.5° size to identify areas with high diversity for the family. Currently the family has 681 species in the Bajío region, distributed in 182 genera; those with the largest number of species are Ageratina (39), Stevia (31), Verbesina (29), and Acourtia (27), whereas 82 genera have one species. On average there are 3.7 species per genus. Querétaro is the state with most species (504), followed by Michoacán (490) and Guanajuato (389). Statistical analyses project 773 species for the studied region of which 681 (88%) have been recorded; from them, at least 66 (67%) have been cited somewhere in the region, but no studied herbarium specimen until now has corroborated their presence. The floristic richness of Asteraceae is evaluated by square grids and several of them are proposed as important in future conservation strategies.